2009
DOI: 10.1152/jn.01235.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Excitability and Neuronal Morphology as Determinants of Synaptic Efficacy

Abstract: Komendantov AO, Ascoli GA. Dendritic excitability and neuronal morphology as determinants of synaptic efficacy. J Neurophysiol 101: 1847-1866, 2009. First published January 28, 2009 doi:10.1152/jn.01235.2007. The ability to trigger neuronal spiking activity is one of the most important functional characteristics of synaptic inputs and can be quantified as a measure of synaptic efficacy (SE). Using model neurons with both highly simplified and real morphological structures (from a single cylindrical dendrite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 49 publications
2
47
0
Order By: Relevance
“…E: tone stimulus. and on the levels and timing of synaptic activity (Komendantov and Ascoli 2009;Migliore et al 2004;Poolos et al 2002;Santoro and Baram 2003). The amplitude of responses to tones decreased in the presence of I h .…”
Section: H and Excitabilitymentioning
confidence: 99%
“…E: tone stimulus. and on the levels and timing of synaptic activity (Komendantov and Ascoli 2009;Migliore et al 2004;Poolos et al 2002;Santoro and Baram 2003). The amplitude of responses to tones decreased in the presence of I h .…”
Section: H and Excitabilitymentioning
confidence: 99%
“…Synaptic efficacy reflects the ability of an individual synaptic input to evoke somatic postsynaptic potentials sufficient to trigger, or alter spiking activity (Komendantov & Ascoli, 2009). Even simple forms of synaptic regulation can have a profound effect on neural function.…”
Section: Activation Of Peripheral Receptorsmentioning
confidence: 99%
“…It has been shown that with the same active and passive properties of the dendritic tree, the geometrical (e.g., area) and topological (e.g., partition symmetry) properties strongly influence the neuronal firing patterns and modify the efficacy of back-propagating action potentials or forward propagation of postsynaptic potentials (Duijnhouwer et al, 2001;Sterratt and van Ooyen, 2002;Chklovskii, 2004;van Pelt and Schierwagen, 2004;Gulledge et al, 2005;Timofeeva et al, 2008;Weaver and Wearne, 2008;Katz et al, 2009;Komendantov and Ascoli, 2009).…”
Section: Indexing Terms: Thalamocortical Neurons; Dendritic Arborizatmentioning
confidence: 99%